If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5x+26)=(8x-2)
We move all terms to the left:
(5x+26)-((8x-2))=0
We get rid of parentheses
5x-((8x-2))+26=0
We calculate terms in parentheses: -((8x-2)), so:We get rid of parentheses
(8x-2)
We get rid of parentheses
8x-2
Back to the equation:
-(8x-2)
5x-8x+2+26=0
We add all the numbers together, and all the variables
-3x+28=0
We move all terms containing x to the left, all other terms to the right
-3x=-28
x=-28/-3
x=9+1/3
| 7(8+2y)-8y=14 | | -2(x+3.4)=-3.7 | | 6x−11=19 | | 118=4x+6x+8 | | 7x+9+5x=117 | | 4x+2=20=26 | | 83-2x=53 | | 1/7x+3=1 | | 2x+4=63 | | 36=x+24 | | (4x-5)=6x-21) | | x+2x+x÷2+15=99 | | 4x²+16x-87=-3 | | 4=x/5=1 | | 4x+23=6x-25 | | 10,205+x=21,894 | | 7x-x+9=29+15 | | -4x+2(7x-17)=-154 | | 15y-5=6y+3-y | | x^2+3x+30=160 | | -6x-15=18 | | b+-13=-32 | | -26=-6=5y | | x-4x=1-12 | | -6/5w-2=-10 | | -19+x/5=-7 | | -6x+11x=73=82 | | 73=3x=13 | | 14r−9r=10 | | r+17=5 | | 91=9x+19 | | 2w=8=34 |